The pharmacological evidence of the chang-yan-ning formula in the treatment of colitis - Wei Yu; Yijia Zhang; Cai Kang; Yang Zheng; Xincheng Liu; Zhenghao Liang; Jing Yan (Frontiers Media S.A., 2022)
Ulcerative colitis (UC) is a subtype of inflammatory bowel disease (IBD) and occurs mainly in the colon. The etiology of UC is rather complex and involves various pathological factors, including genetic susceptibility, dietary intakes, environment, and microbiota. In China, the Chang-Yan-Ning (CYN) formula has been utilized in the clinic to treat gastrointestinal disorders, but its pharmacological evidence remains elusive. The investigation was designed to explore the molecular and cellular mechanisms of CYN. Liquid Chromatography with tandem mass spectrometry (LC/MS) was performed to identify the key components in the formula; Network pharmacology analysis was executed to predict the potential targets of CYN; An experimental murine colitis model was established by utilizing 2% dextran sodium sulfate (DSS), and CYN was administered for 14 days. The pharmacological mechanism of the CYN formula was corroborated by in-vivo and in-vitro experiments, and high throughput techniques including metabolomics and 16S rRNA sequencing. Results: LC/MS identified the active components in the formula, and network pharmacology analysis predicted 37 hub genes that were involved in tumor necrosis factor (TNF), interleukin (IL)-17, hypoxia-inducible factor (HIF) signaling pathways. As evidenced by in-vivo experiments, DSS administration shortened the length of the colon and led to weight loss, with a compromised structure of epithelium, and the CYN formula reversed these pathological symptoms. Moreover, CYN suppressed the levels of pro-inflammatory cytokines, including IL-4, IL-1b, and TNFαin the serum, inhibited the protein abundance of IL17 and HIF-1αand increased PPARγ and CCL2 in the colon, and facilitated the alternative activation of peritoneal macrophages. While peritoneal macrophages of colitis mice enhanced reactive oxygen species (ROS) production in murine intestinal organoids, the ROS level remained stable co-cultured with the macrophages of CYN-treated mice. Furthermore, the decreased microbiota richness and diversity and the prevalence of pathogenic taxa in colitis mice were rescued after the CYN treatment. The altered metabolic profile during colitis was also restored after the therapy. We posit that the CYN therapy attenuates the development and progression of colitis by maintaining the homeostasis of immune responses and microbiota.